Students' Attitude Towards Learning Methods for Self-Sufficiency Development in Higher Education - Rutkiene, Ausra; Tandzegolskiene, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The diversity of teaching methods and the change in the teaching paradigm which emphasises a student-directed teaching and holistic approach altered the understanding of the role of the teaching/ learning methods as mediators between lecturers and students. A method is seen not only as a means to master the material of the discipline or to enhance language skills, but also as a complex tool which allows the student to adapt to teaching material, to socialize in a group, to know and evaluate oneself and to develop argumentative and critical thinking. The results show that the most common teaching methods (lecturing, explanation, narration, demonstration) are not active. Active, application and practice oriented teaching methods are relatively rare. With respect to the self-sufficient learning it turned out that students mostly see the value in the possibility to plan their study process, to observe, adjust and evaluate their learning results and process.